Hubungan Antara Aktivitas Bermain Balok Berwarna Dengan Kemampuan Konsentrasi Anak Usia Dini (Penelitian Kuantitatif di Kelompok B RA Al-Ihsan Karawang) - Putri, Nuramaliah Elyanti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine: 1) The activity of playing colored blocks in Group B RA Al-Ihsan Karawang; 2) The concentration ability of early childhood in Group B RA Al-Ihsan Karawang; 3) The relationship between the activity of playing colored blocks and the concentration ability of early childhood in Group B RA Al-Ihsan. Children's concentration ability is influenced by various factors, one of which is the activity of playing colored blocks. Colored blocks are a construction game activity, children can express various ideas in their minds to build various buildings. The method of this study uses a quantitative approach with the correlation method. The subjects of this study were 20 children in Group B of RA Al-Ihsan Karawang. This study used a saturated sampling technique, namely all children in Group B of RA Al-Ihsan Karawang were determined to be research respondents. The data collection technique used interviews or conversations, observation and documentation. The results of the data analysis showed that the activity of playing with colored blocks was included in the very good category with a value of 89 which was in the interval 80-90 and the children's concentration ability was included in the good category with a value of 77 which was in the interval 70-79 and both variables showed a relationship, with a correlation coefficient of 0.37. The correlation coefficient is in the interval 0.200 - 0.399. Meanwhile, the contribution of the activity of playing with colored blocks to the concentration ability of early childhood children is 8%. This means that there are still 92% other factors that influence the concentration ability of children in Group B of RA Al-Ihsan Karawang.